The Influence of Intellectual Capital and Investment Decisions on Company Value - Rina Silitonga; A. Dewantoro Marsono (Green Publisher Indonesia, 2024)
This study aims to determine the influence of intellectual capital and investment decision on firm value. This type of research is correlational, aimed at proving whether there is a relationship between variables as found in previous studies. The population includes all consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the period from 2013 to 2022. The sampling technique used is Purposive Sampling. The population data consists of 290 companies, and a sample of 130 companies was obtained. The data analysis method used is multiple linear regression analysis. The results of the data analysis show that intellectual capital has a positive effect on firm value, and investment decision have a positive effect on firm value. The adjusted R-Square value of 0.1204 indicates that the ability of independent variables to explain the variation in dependent variables is 12.04%, and the remaining 87.6% is explained by other variables outside the research model.